Advances in fuzzy logic and technology 2017 : proceedings of EUSFLAT, 2017, the 10th Conference of the European Society for Fuzzy Logic and Technology, September 11-15, 2017, Warsaw, Poland, IWIFSGN'2017, The Sixteenth International Workshop on Intuitionistic Fuzzy Sets and Generalized Nets, September 13-15, 2017, Warsaw, Poland, volume 2 /: proceedings of EUSFLAT, 2017, the 10th Conference of the European Society for Fuzzy Logic and Technology, September 11-15, 2017, Warsaw, Poland, IWIFSGN'2017, The Sixteenth International Workshop on Intuitionistic Fuzzy Sets and Generalized Nets, September 13-15, 2017, Warsaw, Poland, volume 2. (2018) - Unknown
No abstract available